Analysis of Factors Influencing the Spread of Asian Swine Fever (ASF) Disease in Samosir District, North Sumatera Province - Sitorus, R.T; N. Ginting; A. Trisna; T. Gultom (Talenta Publisher, 2023)
In Samosir, socio-cultural elements are closely related to pig farming and traditional wisdom which makes pig farming an important part of traditional ceremonies for Christians. In 2019 to 2020 ASF disease is spreading on Samosir Island. African Swine Fever (ASF) is a highly contagious viral disease of pigs, causing various internal bleeding and accompanied by a very high mortality rate. This study used a survey method (interviews) and data analysis using multiple linear regression analysis to obtain the factors that influence the cause of the spread of Asian Swine Fever (ASF) in pigs in Samosir Regency. Based on the results of the study it was found that there was a significant effect of the vaccination variable, the biosecurity variable and the livestock transportation variable, while the variables that had no significant effect were the feed variable and the cage variable on the spread of Asian Swine Fever (ASF) in pigs in Samosir Regency